Impact of glycemic status on longitudinal cognitive performance in men with and without HIV infection. (24th August 2018) - Yang, Jingyan; Jacobson, Lisa P.; Becker, James T.; Levine, Andrew; Martin, Eileen M.; Munro, Cynthia A.; Palella, Frank J.; Lake, Jordan E.; Sacktor, Ned C.; Brown, Todd T.
Abstract : Objectives: To determine the relationship between glycemic status and cognitive performance in men living with HIV (MLWH) and without HIV infection. Design: A prospective HIV/AIDS cohort study in four US cities between 1999 and 2016. Methods: Glycemic status was categorized as normal glucose, impaired fasting glucose, controlled diabetes mellitus and uncontrolled diabetes mellitus at each semiannual visit. Cognitive performance was evaluated using nine neuropsychological tests which measure attention, constructional ability, verbal learning, executive functioning, memory and psychomotor speed. Linear mixed models were used to assess the association between glycemic status and cognition. Results: Overall, 900 MLWH and 1149 men without HIV were included. MLWH had significantly more person-visits with impaired fasting glucose (52.1 vs. 47.9%) and controlled diabetes mellitus (58.2 vs. 41.8%) than men without HIV ( P  < 0.05). Compared with men with normal glucose, men with diabetes mellitus had significantly poorer performance on psychomotor speed, executive function and verbal learning (all P  < 0.05). There was no difference in cognition by HIV serostatus. The largest effect was observed in individuals with uncontrolled diabetes mellitus throughout the study period, equivalent to 16.5 and 13.4 years of aging on psychomotor speed and executive function, respectively, the effect of which remained significant after adjusting for HIV-related risk factors. Lower CD4 + nadir was also associated with worse cognitive performance. Conclusion: Abnormalities in glucose metabolism were more common among MLWH than men without HIV and were related to impaired cognitive performance. Metabolic status, along with advanced age and previous immunosuppression, may be important predictors of cognition in the modern antiretroviral therapy era.